Jamur upas (upasia salmonicolor) pada daun kopi di pagilaran: Pink fungus (upasia salmonicolor) on coffee leaves in pagilaran - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1996)
ABSTRACT The results of this study showed that most of fungus as thin mycelial layer on the coffee leaves were connected with pink fungus on the branch The microscopic study showed the hyaline mycelia producing perpendicular branches, and anastomose easily, the hyphal cells contain one to four nuclei. The anatomy ofpink incrustation Â°Limps composed offour [Tiers: I. basal layer